2019
DOI: 10.1002/btpr.2932
|View full text |Cite
|
Sign up to set email alerts
|

A population balance model to modulate shear for the control of aggregation in Taxus suspension cultures

Abstract: Cellular aggregation in plant suspension cultures directly affects the accumulation of high value products, such as paclitaxel from Taxus. Through application of mechanical shear by repeated, manual pipetting through a 10 ml pipet with a 1.6 mm aperture, the mean aggregate size of a Taxus culture can be reduced without affecting culture growth. When a constant level of mechanical shear was applied over eight generations, the sheared population was maintained at a mean aggregate diameter 194 μm lower than the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…One of the most logical and simplest ways to overcome these concerns could be related to the increase in the stirring speed, because it will break the flocs and cell agglomerates, facilitating the substrate and oxygen uptake and, therefore, increasing the growth rate and conversion to desired products [174,181]. Nevertheless, plant cells, as with other micro-organisms, are sensitive to shearing, and surpassing their resistance umbral to hydrodynamic stress may induce their cell wall breakage, causing the loss of valuable products [124,180,182].…”
Section: Considerations Of Cell Culture Properties On the Mixing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most logical and simplest ways to overcome these concerns could be related to the increase in the stirring speed, because it will break the flocs and cell agglomerates, facilitating the substrate and oxygen uptake and, therefore, increasing the growth rate and conversion to desired products [174,181]. Nevertheless, plant cells, as with other micro-organisms, are sensitive to shearing, and surpassing their resistance umbral to hydrodynamic stress may induce their cell wall breakage, causing the loss of valuable products [124,180,182].…”
Section: Considerations Of Cell Culture Properties On the Mixing Processmentioning
confidence: 99%
“…A clear example that the aggregate size is an important parameter for the production of high added-value PDSM is the production of Paclitaxel by Taxus chinensis cultures. The authors of [176,181] showed that mechanical shear helps disintegration, favoring production by having small aggregates (194 µm) compared to the control, in which large aggregates (600 µm) were obtained that directly affected production.…”
Section: Considerations Of Cell Culture Properties On the Mixing Processmentioning
confidence: 99%
“…Furthermore, the taxane and phenylpropanoid biosynthetic pathways could be separately co-regulated by factors outside of methyl jasmonate elicitation, which would explain their unique responses with respect to aggregate size. It was recently reported that shear forces can be used to decrease aggregate size in a predictable and controlled manner, providing opportunity to further engineer the Taxus production system [30]. Application of this technique with transcriptomic analysis could provide a method to further understand the effect of elicitation state and aggregate size especially in pathways other than taxane biosynthesis.…”
Section: The Relationship Between Metabolite Accumulation and Aggregate Sizementioning
confidence: 99%